Activation of APOBEC3 cytidine deaminases and endogenous retroviruses is integrated by MUC1-C in NSCLC cells - Naoki Haratake; Shinkichi Takamori; Hideko Isozaki; Keisuke Shigeta; Chie Kikutake; Hiroki Ozawa; Atrayee Bhattacharya; Ayako Nakashoji; Mikita Suyama; Tomoyoshi Takenaka; Tomoharu Yoshizumi; Atsushi Osoegawa; et al. (Cell Death Discovery)
Abstract The APOBEC3 (A3) genes encoding cytidine deaminases evolved in mammals to restrict retroviral replication. The MUC1 gene appeared in mammals to protect barrier tissues from viral infections. There is no known involvement of the MUC1 encoded MUC1-C/M1C protein in the regulation of A3s. We found that induction of MUC1-C in NSCLC cells treated with EGFR inhibitors integrates activation of an inflammatory memory response with the type I interferon (IFN) STAT1/STAT2/IRF9 (U-ISGF3) pathway. In turn, MUC1-C drives expression of A3 genes by activating their U-ISGF3-stimulated response elements (ISREs). We also report that MUC1-C-mediated induction of type II IFN STAT1 homodimer (U-GAF) complexes and the gamma-associated signaling (GAS) pathway drives human endogenous retrovirus HERV-K102/K108 expression. Our results in NSCLC cell line and patient-derived models further demonstrate that MUC1-C activates A3 and HERV-K expression by a common MUC1-C→STAT1 auto-inductive pathway. These previously unrecognized findings demonstrate that a MUC1-C-driven inflammatory pathway coordinates activation of APOBEC3 and HERV-K expression.